Recurrent Severe Iron Deficiency Anemia and Thrombocytopenia in an Adolescent Male. Issue 2 (March 2019) - Giordano, Lisa; Llanos-Chea, Alejandro; Monde, Alexandra; Mulinge, Ivy; Dighe, Dipti
Abstract : An adolescent male presented with recurrent episodes over several years of severe iron deficiency anemia and associated severe thrombocytopenia. The anemia was secondary to chronic blood loss due to ulceration at the site of an ileocolonic anastomosis performed during infancy. We were able to demonstrate complete resolution of thrombocytopenia with the administration of iron, and without using steroids, intravenous immunoglobulin, or platelet transfusions. This is the first reported case of an individual with multiple episodes over several years of thrombocytopenia secondary to recurrent severe iron deficiency anemia, illustrating a predisposition to this complication in a unique patient.